Environmental Valuation With Periodical Payments in High-inflation Economies. An Argentinean Case Study - Farreras González, Verónica Inés (2017)
Stated preference valuation surveys often ask respondents for periodical payments, sometimes for the remaining life of the individuals. Questionnaires do not usually specify whether those payments would vary according to inflation. This may be less important in low-inflation economies, but results could differ significantly in high-inflation countries. A contingent choice exercise was conducted to explore the severity of this effect in Argentina. The empirical application focused on an anthropogenic-pressure mitigation program for the basins of the Mendoza region. A comparison of willingness-to-pay results from a scenario where annual payments were to be increased according to inflation with another of fixed annuities, found inflation to be significantly influential on respondents' stated values. Furthermore, a test on the robustness of the estimated values found results to be consistent with prior expectations.